Pengaruh Ukuran Partikel Zeolit Alam yang Diaktivasi dan Diimpregnasi HCl dan Mg2+ pada Penjerapan Ion Fosfat - Fatimah; Effendi, Sri Rahmadaniati; Sofith, Charissa Dini (Jurnal Teknik Kimia USU, 2021)
Research on phosphate adsorption using natural zeolites which were activated and impregnated with HCl and Mg2 +had been carried out. This study examined the effect of natural zeolite particle size on phosphate ion adsorption. Stages of the study began from sifting zeolites in accordance with the specified size (50/70 mesh, 70/110 mesh and 110/120 mesh), washing, activation and impregnation. Natural zeolite with 110/120 mesh particle size is used to determine the contact time in absorbing phosphate ions. Natural zeolite can absorb phosphate as much as 8.53 mg / l or 85.3% with a contact time of 35 minutes. The variation of the adsorption on the natural zeolite particle size is carried out to get the effect of the natural zeolite particle size on the adsorption of phosphate ions. Phosphate ions which are absorbed by zeolites are analyzed using a UV-Vis spectrophotometer. The highest absorption efficiency (99.26%) was obtained for natural zeolite particle size 110/120 mesh. The natural zeolite adsorption isotherm model of the phosphate ion is tested with the Freundlich and Langmuir equations. Based on the data obtained, the isotherm model suitable for this study is Freundlich with a value of R2 = 0.985.